Biotecnologia aplicada à segurança pública: estudo e adequação do método da ninidrina para revelação de impressões digitais em superfícies porosas - Alves, Manoel Geralcino (Universidade Federal de São Carlos, 2013)
Several works have been done worldwide and are dedicated to the advancement of software that enables the comparison and reading of fingerprints. Literature shows several works related to the development of scientific techniques that allow the improvement in the collection and disclosure of fingerprints left at crime scenes. Some of those techniques are based on the use of high-tech materials and devices, such as gold nanoparticles and thin films made of copper and gold. However, the cost of these techniques is very high for everyday use, especially when considering the financial budgets for police apparatus in developing countries. Attempting to improve economically such viable and efficient techniques in order to permit the disclosure of latent fingerprints left at crime scenes, this work aims the studying and development of the ninhydrin colorimetric method, by performing numerous tests on fingerprints deposited on porous surfaces, such as paper and walls. Once confirmed the viability of ninhydrin employment, both in laboratory and on-site, and also having adjusted the optimum temperature for rapid revelation; this study provides the use of image-processing software, enabling the expert to compare, in real time, even at the site of criminal traces, the fingerprint image found with the official registry database, thus, obtaining the identity of the offender within a short period of time.
Keywords: Biotecnologia; Identificação biométrica; Datiloscopia; Ninidrina; Impressão digital; Identificação Humana; Biotechnology; Human identification; Digital printing; Ninhydrin; OUTROS